2021
DOI: 10.1029/2021gl096020
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Eddies Regulate Seasonal Iron Supply and Carbon Drawdown in the Drake Passage

Abstract: The Southern Ocean plays a critical role in the global carbon cycle. The dominating current in the region, the Antarctic Circumpolar Current (ACC), circumnavigates the globe and connects all of the major ocean basins. Its overturning circulation brings up the deepwater and subducts thermocline and intermediate waters that are major conduits for the oceanic uptake of heat and anthropogenic carbon (Armour et al., 2016; Ben Bronselaer & Zanna, 2020;Toggweiler & Russell, 2008), contributing over 40% of the ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…showed that mesoscale resolving models may have a modest effect on the global balance of carbon export (<2%), but regionally the effect can be large (±50%). Jersild et al (2021) highlighted that an Earth System Model (ESM) that explicitly resolved mesoscale eddies was able to produce the observed seasonal biological productivity and pCO2 (sw) cycles in the Southern Ocean, but when the eddies were not included, the seasonal cycle was not well reproduced. The results from our study have significant implications on the air-sea CO2 flux in current global ESMs, in which eddies are not explicitly resolved (Hewitt et al, 2017(Hewitt et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…showed that mesoscale resolving models may have a modest effect on the global balance of carbon export (<2%), but regionally the effect can be large (±50%). Jersild et al (2021) highlighted that an Earth System Model (ESM) that explicitly resolved mesoscale eddies was able to produce the observed seasonal biological productivity and pCO2 (sw) cycles in the Southern Ocean, but when the eddies were not included, the seasonal cycle was not well reproduced. The results from our study have significant implications on the air-sea CO2 flux in current global ESMs, in which eddies are not explicitly resolved (Hewitt et al, 2017(Hewitt et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we are optimistic that a suitably chosen eddy parameterization will lead to additional improvements of our results, in particular for the general circulation and tracer distribution in the open ocean. The incorporation of subgridscale eddy activity was shown to impact temperature, salinity and sea ice formation in high latitudes (e.g., Knutti et al., 1999; Pradal & Gnanadesikan, 2014) as well as nutrient replenishment in the upper thermocline of oligotrophic subtropical waters (Doddridge & Marshall, 2018; Oschlies, 2008) and seasonal carbon drawdown in the eddy‐rich Southern Ocean (Jersild et al., 2021). The sediment resuspension scheme of ICON‐Coast accounts for the bottom layer thickness in the calculation of the sediment drag coefficient, thus accounting for the vertical grid resolution (Mathis et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we are optimistic that a suitably chosen eddy parameterization will lead to additional improvements of our results, in particular for the general circulation and tracer distribution in the open ocean. The incorporation of subgridscale eddy activity was shown to impact temperature, salinity and sea ice formation in high latitudes (e.g., Knutti et al, 1999;Pradal & Gnanadesikan, 2014) as well as nutrient replenishment in the upper thermocline of oligotrophic subtropical waters (Doddridge & Marshall, 2018;Oschlies, 2008) and seasonal carbon drawdown in the eddy-rich Southern Ocean (Jersild et al, 2021). The sediment resuspension scheme of ICON-Coast accounts for the bottom layer thickness in the calculation of the sediment drag coefficient, thus accounting for the vertical grid resolution (Mathis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%